The Effect of Tri Hita Karana Local Wisdom on Financial Performance of UP3HP Jempiring Group in Regency Badung - Ni Wayan Surya Suryathi; Made Antara; Nengah Bawa Atmaja; Wayan Windia (SEAS (Sustainable Environment Agricultural Science), 2018)
Every business group that is in the community, if run in earnest, tenacious, enterprising, and honest matters, will usually succeed in achieving its goals. The Jempiring Group of Service Unit, Development and Processing of Agricultural Products (UP3HP) in Badung regency obtain capital assistance from the Government and required to be accountable to the government as a form of success/ group’s performance in running its business. The purpose of this study is to determine the influence of local wisdom Tri Hita Karana on financial performance UP3HP Jempiring Group in Badung regency. The result and discussion show that local wisdom Tri Hita Karana have a strong influence on Financial Performance of UP3HP Jempiring Group in Badung regency. This is because Tri Hita Karana has penetrated each member of the UP3HP Jempiring group in the implementation of the community both in religious ceremonies, such as the ceremony of Dewa Yadnya, Manusa Yadnya, Pitra Yadnya or Butha Yadnya, menyamebraya activity, as well as its existence in preserving plants related with the processing of agricultural produce.